The Relationship Between Cash Conversion Cycle and Profitability in Medium-Sized Real Estate and Property Firms Listed in The Indonesia Stock Exchange (IDX) - Dondokambey, Griffit Yoyner; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2015)
Abstract.The objective of the research is to examine the impact of CCC’s components on the profitability of Indonesia medium sized real estate and property firms. The research used the samples of eight companies listed on Indonesia Stock Exchange period of 2008-2012, selected by purposive sampling method based on criteria of Medium Enterprise according to UU No. 20 Tahun 2008 Tentang Usaha Mikro, Kecil, dan Menengah. Pearson Product Moment Correlation and Multiple Linear Regression were used to examine the relationship of CCC’s components: (Average Age of Inventory (AAI), Average Collection Period (ACP), And Average Payment Period (APP) on the firm’s profitability (Earning Per Share (EPS). The findings of this research show that AAI partially has negative relationship on firm profitability, but it is not statistically significant. ACP and APP partially have negative relationship and significant effect on a firm’s profitability. Simultaneously, AAI, ACP, and APP have positive relationship and significant effect on a firm’s profitability. These findings imply that Medium-sized real estate and property firm need to focus on managing ACP and APP in order to improve their profitability.Keywords: Real estate dan property, Small Medium Enterprise (SME), Cash Conversion Cycle(CCC)